Dilatapalochrus gen. nov.—a new species and a new genus of soft-winged flower beetle of the tribe Apalochrini (Coleoptera: Malachiidae) from East Africa - Tshernyshev, Sergei E. (Zootaxa, 2021)
A new genus, Dilatapalochrus Tshernyshev gen. nov., from East Africa is described in the tribe Apalochrini with Dilatapalochrus vikhrevi Tshernyshev, sp. nov. designated at the type species. Male external appearance and special male characters for the new species are illustrated. Placement of the genus in the tribe Apalochrini is discussed, and a key to genera of the tribe occurring in Africa is provided.